2010
DOI: 10.1111/j.1399-0004.2009.01356.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutation detection rate and spectrum in familial hypercholesterolaemia patients in the UK pilot cascade project

Abstract: Cascade testing using DNA-mutation information is now recommended in the UK for patients with familial hypercholesterolaemia (FH). We compared the detection rate and mutation spectrum in FH patients with a clinical diagnosis of definite (DFH) and possible (PFH) FH. Six hundred and thirty-five probands from six UK centres were tested for 18 low-density lipoprotein receptor gene (LDLR) mutations, APOB p.Arg3527Gln and PCSK9 p.Asp374Tyr using a commercial amplification refractory mutation system (ARMS) kit. Sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
141
2
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(162 citation statements)
references
References 43 publications
15
141
2
4
Order By: Relevance
“…It is well known that only some patients with clinically diagnosed FH have pathogenic mutations in LDLR, APOB, or PCSK9 10,12,17) . In the KSLA-supported study, the largest Korean FH study to date, putative mutations in these 3 genes were found in 32% of the enrolled patients.…”
Section: Genetic Characteristicsmentioning
confidence: 99%
“…It is well known that only some patients with clinically diagnosed FH have pathogenic mutations in LDLR, APOB, or PCSK9 10,12,17) . In the KSLA-supported study, the largest Korean FH study to date, putative mutations in these 3 genes were found in 32% of the enrolled patients.…”
Section: Genetic Characteristicsmentioning
confidence: 99%
“…Overall, CHD risk was independently related to age, sex, smoking, previous CHD and total cholesterol, but after adjustment for these variables the higher CHD risk in DFH compared to PFH patients was no longer statistically significant. Since we know that up to 80% of those with clinical DFH will carry an FH-causing mutation [13,14] while probably 80% of those with clinical PFH have a polygenic aetiology of their hyperlipidaemia [15,16], this confirms reports that carriage of an FH mutation is associated with greater CHD risk [4]. This higher risk is supported by the observation that, even though LDL-C levels were similar, compared to those with polygenic hypercholesterolaemia, those with an FH-causing mutation have greater carotid intimalmedial thickening and coronary calcification [24].…”
Section: Discussionmentioning
confidence: 99%
“…While in DFH patients an FH-causing mutation can be identified in about 80% of subjects, this falls to only 20e30% in PFH patients [13]. In the majority of patients with a clinical diagnosis of FH but with no detectable mutation in any of the three common genes [14], it is now widely accepted that there is a polygenic cause for their raised LDL-C level [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Bei 93 % der Betroffenen liegen die verantwortlichen Mutationen im Gen des LDL-Rezeptors (LDL-R; [27, 52, 54]), bei 5 % findet man Mutationen der rezeptorbindenden Domäne des Apolipoproteins B-100 (APOB-100; [45,47]) und bei 2 % "Gain-of-function"-Mutationen von PCSK9 ("proprotein convertase subtilisin/kexin type 9"; [1,36,68,[71][72][73]). PCSK9 ist eine Protease, die am zellulären Abbau von LDLR beteiligt ist.…”
Section: Autosomal-dominante Familiäre Hypercholesterinämieunclassified